Evaluating the Practical Value of Voice-Controlled E-Dictionary Teaching Media for Science Education at the Elementary School Level - Rades, Radeswandri; Rian, Rian Vebrianto; Musa, Musa Tahir; Yovita, Yovita; Irfan, Irfan andi Gafur (Universitas Pendidikan Ganesha, 2025)
The Education Curriculum in Indonesia is reforming in accordance with the development of World Innovation, covering political, economic, social, cultural, and technological aspects. These reforms are to improve competitiveness and human resources who possess quality, synergize, and behave ethically so the education ecosystem in the future is maintained to minimize the negative impacts caused. The current industrial progress in the 21st century has entered the stage of industry 4.0 and society 5.0 aiming to facilitate human performance and strengthen social relations in the world's society. This study aimed to apply of E-Dictionary Teaching Media based on Voice Control Recognition (VCR) from the practical aspect. This study used Research and development design with a mixed-method with a total sample of 64 teachers and 52 students. Data collection techniques included a questionnaire, interview, and documentation. The data obtained were analyzed descriptively and inferentially to assess practicality including Ease (of use), Presentation, Readability, and Efficiency and Effectiveness. The results showed that of the 5 practicality indicators, the Effectiveness indicator by students is higher than the Presentation indicator by teachers. However, in general, the practicality performance has met the standard of usability assessment.